Pengembangan Media Games IPA Edukatif Berbantuan Aplikasi Appsgeyser Berbasis Model PBL untuk Meningkatkan Karakter Peduli Lingkungan Siswa Sekolah Dasar - Widya Indra; Yanti Fitria (Universitas PGRI Madiun, 2021)
This type of research is development. The development model used is a 4-D model, consisting of four stages, namely defining, designing, developing, and deploying. The research data obtained from validity, practicality and rights testing. Data collected descriptively. The results showed that the development of educational science game media with the help of the AppsGeyser application based on the Problem Based Learning model to improve the environmental care character of the fifth grade elementary school students developed had met valid, practical and effective criteria with (1) media validity test results, namely the media aspect, the material and language score in the very good category, the validity test of the lesson plan scores in the very good category, and the validity test for the character of environmental care obtains a score in the valid and very valid category (2) the results of the practicality test of instructional media by the teacher and students obtained the value in the very practical category. (3) the results of the effective test in the form of learning outcomes, namely the cognitive, affective, and psychomotor domains each obtained an average score of 84, 83, and 85 in the very good category, and the results of the early student environmental character effectiveness test obtained an average value. 73.9 and 86.6 for the average score in the category are very effective.